2014
DOI: 10.5539/gjhs.v7n4p18
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Illicit Drug Use Among University Students in Northern Ireland, Wales and England

Abstract: Introduction:The use of illicit drug/s among university students is a public health concern. Nevertheless, many UK studies investigated a narrow spectrum of variables to explore their association/s with illicit drug/s use.Methods:We assessed the associations between a wide range of socio-demographic, health and wellbeing variables (independent variables) and having used illicit drug/s regularly, occasionally or never in life (dependent variables). Data (3706 students) were collected from seven universities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
80
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 39 publications
15
80
2
3
Order By: Relevance
“…We found a wide range of the prevalence of illicit drug use ranging from as low as 0.2% in Cambodia to as high as 46% in Laos for infrequent use and from 0.0% in Cambodia to 5.5% in Laos for frequent use in the past 12 months. Overall, the prevalence of illicit drug use among university students across the nine ASEAN countries is considerably high and comparable with the prevalence rates reported in other countries [15, 17, 20, 22]. This finding supports the global concern that illicit drug use in university students is a significant public health issue that requires particular attention [32].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We found a wide range of the prevalence of illicit drug use ranging from as low as 0.2% in Cambodia to as high as 46% in Laos for infrequent use and from 0.0% in Cambodia to 5.5% in Laos for frequent use in the past 12 months. Overall, the prevalence of illicit drug use among university students across the nine ASEAN countries is considerably high and comparable with the prevalence rates reported in other countries [15, 17, 20, 22]. This finding supports the global concern that illicit drug use in university students is a significant public health issue that requires particular attention [32].…”
Section: Discussionsupporting
confidence: 77%
“…Peltzer and Pengpid, using data collected in eight countries in Africa and three countries in the Caribean, reported that the prevalence of infrequent (1–9 times) and frequent (≥10 times) illicit drug use in the past 12 months was 17 and 4%, respectively [19]. In the United Kingdom, 5% of the study sample from seven universities reported regularly using illicit drugs, and 25% reported occasional use of them [20]. Only a few studies have been conducted in Asian countries, and information on types of illicit drugs included in the studies were limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is overwhelming consensus that religiosity, particularly attendance and often spirituality, are negatively related to alcohol, tobacco, and illicit substance use across the U.S. and other countries (El Ansari et al, 2014; Hatta, 2010; Hayatbakhsh et al, 2014; Kovaks et al, 2011; Rasic et al, 2011; Wang et al, 2015). Recent comprehensive reviews concluded that RS consistently negatively predicted substance use, possibly due in part to prohibitions against alcohol and other substance use inherent in some religions (Geppert et al, 2007; Kub & Solari-Twadell, 2013; Walton-Moss et al, 2013; Yeung et al, 2009); however, many cited studies did not control for possible confounds such as income or education.…”
Section: Rs and Health Research: Current Findings And Critiquementioning
confidence: 99%
“…A study of seven universities in the United Kingdom reported 5% students sampled regularly using illicit drugs, and 25% being occasional users [23]. Another similar study in Wales reported common substances abused by university students were alcohol, cigarettes, cannabis, ecstasy, nitrous oxide and cocaine (2017).…”
Section: Substance Use Disorders Among University Students In Europementioning
confidence: 98%